Organic Facial Mask Formulation From Coffee Beans (Coffea Sp) And Rice Flour (Oryza sativa) - Indrasari, Delfi Sri; Wa Ode Syafriah; Muhammad Tasjiddin Teheni (International Journal of Multidisciplinary Learners, 2024)
The natural ingredients used are coffee beans (Coffea SP) and rice flour (Oryza Sativa). The objective of this study is to determine the method of making a natural mask from coffee beans and rice flour, and to test the physical properties of a face mask made from a combination of coffee bean powder and rice flour. The research method used is experimental or laboratory testing. The best result from the face mask preparation is Formula I, with a combination of 30% rice flour and 70% coffee bean powder. The evaluation of the face mask preparation from the combination of coffee bean powder and rice flour in Formula I shows that the powder is slightly coarse, has a scent, and is brown in color. The mixed ingredients are homogeneous, with a normal pH of 4, and the drying time during application is 10 minutes. The conclusion of this study is that the best concentration for the face mask preparation is Formula I, with a combination of 70% coffee bean powder and 30% rice flour. The evaluation of the face mask preparation from the combination of coffee bean powder and rice flour in Formula I shows that the powder is slightly coarse, has a scent, and is brown in color. It has a normal pH of 4, and the drying time during application is 10 minutes.